Handbook of research on nascent entrepreneurship and creating new ventures - Moreira, António Carrizo; Dantas, Jose Guilherme Leitao, 1955- (Advances in business strategy and competitive advantage., 2021)
"This book defines nascent entrepreneurship as the process of creating of a new business venture and provides entrepreneurs, researchers and the business world with a publication on the contribution of nascent entrepreneurship to the business world"--